The Effect of Images in Writing Spoof Texts on Students’ Ability of Grade XI at SMA Negeri 1 Pematangsiantar - Sinaga, Yanti Kristina; Hutahaean, David Togi (Innovative: Journal Of Social Science Research, 2025)
This study investigates the impact of visual media, specifically images, on Grade X students’ ability to write spoof texts at SMA Negeri 1 Pematangsiantar. Using a quasiexperimental design with a pretest-posttest nonequivalent group format, 62 students were divided into an experimental group receiving image-based instruction and a control group taught without visual aids. The experimental group demonstrated significant improvement, with mean scores increasing from 51.26 in the pretest to 84.74 in the posttest, compared to the control group’s modest increase from 50.39 to 66.65. The t-test analysis confirmed the results were statistically significant (t-value = 6.06, p < 0.05). Visual media enhanced students’ understanding of spoof text structures, including orientation, events, and twists. It also fostered creativity and narrative cohesion, enabling students to construct engaging and coherent stories. In contrast, traditional instruction showed limited effectiveness in improving these skills. The findings highlight the benefits of integrating visual aids into English instruction, particularly for creative writing tasks. Images serve as effective scaffolding tools, helping students organize ideas and improve writing quality. This study underscores the potential of visual media to enhance students’ creative abilities in narrative genres, emphasizing its importance in educational practices.